Antibiotic Prophylaxis Prescribing Practices for Dental Implant Placement in Croatia: A Questionnaire-Based Cross-Sectional Study - Mare Ković; Ajka Pribisalić; Joško Viskić; Jure Martinić; Josipa Grubišić; Ante Vardić; Tina Poklepović Peričić (Antibiotics)
Background/Objectives: This study aimed to explore antibiotic prescribing practices for dental implant placement in Croatia. Methods: We conducted a cross-sectional questionnaire-based study including dentists in Croatia who perform dental implant therapy. The questionnaire assessed the dentists’ age, working experience, education level, and whether they use antibiotics for dental implant placement, as well as the choice of antibiotics, timing, and reasons for antibiotics use. We used snowball and convenient sampling methods for recruiting dentists. Categorical data were described as absolute numbers and percentages. Differences in the use of antibiotics for specific health conditions were analyzed using Chi-Square, with p < 0.05. Results: Overall, 74 dentists completed the survey. The dentists used antibiotics either before and after (N = 37, 48.7%), before (N = 21; 27.6%), or after dental implant placement (N = 17, 22.4%). Most used Amoxicillin (N = 47, 61.8%), or Amoxicillin–clavulanic acid (N = 22, 28.9%). Almost all dentists used antibiotics in patients with artificial heart valves (N = 73, 97.3%) and a history of infective endocarditis (N = 74, 98.7%). Also, the dentists reported using antibiotics in patients with artificial joints (N = 52, 69.3%), diabetes (N = 48, 64%), HIV (N = 51, 34.2%), or those on antiresorptive drugs (N = 46, 61.3%), with 17 dentists (22.7%) prescribing antibiotics to all (p < 0.001). The main reasons for antibiotic prophylaxis were preventing complications at the implant site (N = 56; 73.7%) and reducing the early implant failure rate (N = 32; 42.1%). Around one-third of the dentists (34.2%) used antibiotics for their own safety. Conclusions: Croatian dentists may be overprescribing antibiotics during dental implant placement. Clear recommendations concerning antibiotic prophylaxis for dental implant therapy are needed to make well-informed clinical decisions.